(untitled) (Itinera, 2015)
This paper is aimed at clarifying the connection between two notions that are inherently related in Hegel’s philosophy, namely system and freedom. I will show how these two notions are mutually supportive, that is to say, they imply one another. I believe this dynamic can shed light on the relationship between rationality and improvisation. More specifically, through the discussion of the relationship between freedom and system, that is, the relationship between freedom and reason, I will investigate the peculiar form of rationality that is active in the practice of conscious improvisation. Moreover, I will explore the inherent necessity enlivening and constituting the experience of freedom that is embodied in this practice.